A Comprehensive Simulation of Solar Wind Formation from the Solar Interior: Significant Cross-field Energy Transport by Interchange Reconnection near the Sun - Haruhisa Iijima; Takuma Matsumoto; Hideyuki Hotta; Shinsuke Imada (The Astrophysical Journal Letters, 2023)
The physical connection between thermal convection in the solar interior and the solar wind remains unclear due to their significant scale separation. Using an extended version of the three-dimensional radiative magnetohydrodynamic code RAMENS, we perform the first comprehensive simulation of the solar wind formation, starting from the wave excitation and the small-scale dynamo below the photosphere. The simulation satisfies various observational constraints as a slow solar wind emanating from the coronal hole boundary. The magnetic energy is persistently released in the simulated corona, showing a hot upward flow at the interface between open and closed fields. To evaluate the energetic contributions from Alfvén wave and interchange reconnection, we develop a new method to quantify the cross-field energy transport in the simulated atmosphere. The measured energy transport from closed coronal loops to open field accounts for approximately half of the total. These findings suggest a significant role of the supergranular-scale interchange reconnection in solar wind formation.